(untitled) (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Arts Humanities Series, 2026)
This research addresses the problem of cyberbullying, which has become a significant psychological and social threat and problem following the widespread use of communication technologies and social media platforms. The research aims to determine the role of family media literacy in protecting adolescents from cyberbullying and its effects. The study employs a descriptive-analytical approach and uses a questionnaire to collect data. The sample consisted of 50 adolescents aged 12 to 19 in the city of Latakia. The findings revealed that 70% of the sample had experienced bullying, while 30% had not. There were no gender differences in exposure to cyberbullying; both males and females were affected. However, there were differences in understanding cyberbullying based on age. Furthermore, awareness of the forms of bullying is not limited to any particular gender, as the social media platforms where bullying occurs are accessible to everyone. The research concludes with the necessity of integrating media literacy into educational curricula, implementing intensive awareness programs for both parents and children, and strengthening cooperation between media, educational, and community institutions to cultivate a generation capable of confronting this social phenomenon.